An Experimental Investigation on RC Concrete Beam by Replacing Steel Reinforcement: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Recently, with respect to increasing problem of global warming, the manufacturers prefer natural materials. Bamboo is low cost, naturally fast growing and easily available so expected to contribute in earthquake-resistant construction the developing countries. RC concrete is commonly used everywhere but it become expensive when steel is use as reinforcement. The intention of research is to use bamboo as a key structural material, for a safe and durable house, which can be affordable by poor people. The concrete is widely used construction material in the world. It has very good compressive strength but it is weak in tension. To fulfill this tensile strength of concrete we are using concrete and steel in all structural members. RCC Structure becomes more expensive due to steel bars use in the structural members. So it is present requirement to find out some alternate for steel reinforcement bars. Bamboo can replace reinforcement bars in low cost housing.